PENGARUH PENERAPAN ETNOMATEMATIKA KUE TRADISIONAL JAWA TERHADAP PENALARAN MATEMATIS SISWA MATERI SIFAT BANGUN RUANG KELAS II SDN ANGGASWANGI II - Fira Ayundasari; Dian Kusmaharti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Ethnomathematics learning in elementary school has significant potential to increase students' interest and understanding of mathematical reasoning skills, especially on the material of building space. This study aims to determine whether there is an effect of the application of ethnomathematics of Javanese traditional cakes on students' mathematical reasoning on the material of the properties of building spaces for grade II SDN Anggaswangi II students. This research is a quantitative study with a research design, namely Quasi eksperimental using post-test only control group design. The population in the study amounted to 66 students. The sample selected in this study was taken with a saturated sample technique where all members of the population were sampled. The samples in this study were class II-A with 33 students as the experimental class and class II-B as the control class with 33 students. The data collection method used was a test using a test sheet. Using the statistical analysis method used, namely the T test (independent sample t-test) with the prerequisite test of normality test and homogeneity test using the SPSS version 21 application.Based on the results of the study, it can be concluded that there is an effect of the application of ethnomathematics of traditional Javanese cakes on students' mathematical reasoning on the material of the properties of class II SDN Anggaswangi II.